A biomimetic peptide has no effect on the isotopic fractionation during in vitro silica precipitation - Lucie Cassarino (Nature Portfolio, 2021)
Abstract The stable isotopic composition of diatom silica is used as a proxy for nutrient utilisation in natural waters. This approach provides essential insight into the current and historic links between biological production, carbon cycling and climate. However, estimates of isotopic fractionation during diatom silica production from both laboratory and field studies are variable, and the biochemical pathways responsible remain unknown. Here, we investigate silicon isotopic fractionation through a series of chemical precipitation experiments that are analogous to the first stages of intracellular silica formation within the diatom silicon deposition vesicle. The novelty of our experiment is the inclusion of the R5 peptide, which is closely related to a natural biomolecule known to play a role in diatom silicification. Our results suggest that the presence of R5 induces a systematic but non-significant difference in fractionation behaviour. It thus appears that silicon isotopic fractionation in vitro is largely driven by an early kinetic fractionation during rapid precipitation that correlates with the initial amount of dissolved silica in the system. Our findings raise the question of how environmental changes might impact silicon isotopic fractionation in diatoms, and whether frustule archives record information in addition to silica consumption in surface water.